(3cJGH RHOI GdWHs - (3ESeGYjd Hf MSjf GdMSjfj, CHh EHQGgje, Rjf GdOjf GdLQLGfj,J (B531 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg JYGdi aCYde Cf eHfi GdWH Ydi eYQaI MGdJi GdEfSGf ef GdMUI hGdeQV s
(3BNQgG (B:s
(3SGe CHQUi jScf GdhLY Ke eUQ GdehVY hjhVY ai eGA HGQO Je GdcJGH s
(3HgG LOGhds
(3HBNQg fbhds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
Keywords: (3GdWHs